EFFECT OF THICKNESS LAYER OF KENAF FIBRE REINFOECED FIBRE GLASS, AGAINST IMPACT OF HYBRID COMPOSITE SANDWICH WITH CORE SENGON - Agung - Mataram; Narwi Panggar Besi (Universitas Sriwijaya, 2019)
The purpose of this research is to know the impact strength of composite structures of sengon laut sawdust. Experimental results show that the impact toughness of sandwich composite will increase as the thickness of composite sandwich skin increases. The impact failure is due mostly to the shear failure of the core. Brittle specimen failure occurs on the sandwich composites structured with skin and core manufactured with the same thickness of 5 mm. This brittle sandwich composite has a flat cross section on both sides of the fault. The shear failure of the cores occurs in samples with 2 mm thick, 3 mm, 4 mm thick, and 10 mm thick core. In some samples, the shear failure of the cores is accompanied by cracks on the core so that the sandwich composite is broken in several parts. The highest value of absorption energy and the highest impact strength is found on thick composite sandwich variation of 10 mm thick with 4 mm thickness of 2,7860 J and 0,01032 J/mm2.